Marriage and Divorce in India : changing concepts and practices - Marriage and Divorce in India (Manohar Publishers, 2019)
Contributed articles presented at the National Seminar on "Marriage and Divorce in a Globalized Era: Shifting Concepts and Changing Practices in India" held at Vadodara from 10-11, April, 2015 at Centre for Culture and Development, Vadodara, India.